Pengaruh Motivasi Belajar, Minat Belajar, Keadaan Sosial Ekonomi Keluarga Siswa Terhadap Prestasi Belajar Kelas X dalam Menempuh Program Keahlian Teknik Komputer Jaringan (Studi pada: SMK Negeri 2 Malang) - Indah Puspitasari; Faizatul Amalia; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Computer and Network Engineering (TKJ) in one of the skills programme at State Vocational High School 2 Malang. Successful learning process could be known by student's learning achievement. Learning achievement could be influenced by several factors, which are motivation, learning interenst, and family socio-economic condition in this research. So this study aims to determine the effect of motivation, learning interest and socio-economi condition towards learning achievement, by individually and simultaneously analysis. The subject of this study were grade X students of TKJ skills programme. The population were 106 students and sample used was 30 students with simple random sampling technique. Analysis used were descriptive analysis, classic assumption tests include normality test, linearity test, multicollinearity test, heteroscedasticity test and autocorrelation test. As well as hypothesis testing carried out by simple linear regression test and multiple regression. The results concluded that learning interest, learning motivation and socio-economic conditons have no effect toward learning achievement. As well as by simultaneously analysis between learning motivation, learning interest and socio-economic conditions don't effect learning achievement. Hence, Ho is accepted and Ha is rejected. It could be seen from the results of the significance values consecutively, which are: 0.91> 0.05; 0.67> 0.05; 0.12> 0.05 and 0.47> 0.05.